2012
DOI: 10.1038/oby.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial of a Commercial Diet and Exercise Weight Loss Program in Minority Breast Cancer Survivors

Abstract: Objective-Obesity is associated with poorer breast cancer outcomes and losing weight postdiagnosis may improve survival. As Hispanic and black women have poorer breast cancer prognosis than non-Hispanic whites diagnosed at similar age and stage, and have higher rates of obesity, effective weight loss strategies are needed. We piloted a randomized, waitlist-controlled, crossover study to examine the effects and feasibility of the commercial Curves weight loss program among Hispanic, African American and Afro-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(88 citation statements)
references
References 30 publications
1
87
0
Order By: Relevance
“…One study was limited to a subgroup of breast cancer survivors, broadly defined as those with estrogen receptor (ER) -positive tumors, 18 and two exclusively recruited African American or Hispanic women. 11,12 Five studies reported mean time since diagnosis at baseline, with this ranging from 3.5 to 5.6 years. [10][11][12]14,18 Interventions varied considerably in their behavioral targets, delivery, and duration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was limited to a subgroup of breast cancer survivors, broadly defined as those with estrogen receptor (ER) -positive tumors, 18 and two exclusively recruited African American or Hispanic women. 11,12 Five studies reported mean time since diagnosis at baseline, with this ranging from 3.5 to 5.6 years. [10][11][12]14,18 Interventions varied considerably in their behavioral targets, delivery, and duration.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Five studies reported mean time since diagnosis at baseline, with this ranging from 3.5 to 5.6 years. [10][11][12]14,18 Interventions varied considerably in their behavioral targets, delivery, and duration. Six trials targeted both diet and physical activity, [10][11][12][13][14][15] with the remaining four addressing dietary intake only.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of weight loss trials in breast cancer survivors reported a total of 10 randomised controlled trials and four single-arm trials have evaluated interventions of two to 18 months in duration, with approximately half reporting mean successful weight loss of at least 5% at end-of-intervention . Of the two trials that reported maintenance outcomes following end-of-intervention, one reported ongoing weight loss at three-months follow-up (Campbell et al, 2012) while the other reported nearly half of initial weight loss was regained at six-months follow-up (Greenlee et al, 2013). The recently published Lifestyle Intervention in Adjuvant Treatment of Early Breast Cancer (LISA) trial randomised breast cancer survivors to a two-year weight loss intervention and reported participants lost an initial 5.3% of weight at six-months, but regained 65% of initial weight loss by two-years follow-up (Goodwin et al, 2014).…”
Section: Weight Loss Interventions In Breast Cancer Survivorsmentioning
confidence: 99%